Parasitological Confirmation and Analysis of Leishmania Diversity in Asymptomatic and Subclinical Infection following Resolution of Cutaneous Leishmaniasis. - Mariana Rosales-Chilama; Rafael E Gongora; Liliana Valderrama; Jimena Jojoa; Neal Alexander; Luisa C Rubiano; Alexandra Cossio; Emily R Adams; Nancy G Saravia; María Adelaida Gomez (Public Library of Science (PLoS), 2015)
BACKGROUND:The contribution of individuals with subclinical infection to the transmission and endemicity of cutaneous leishmaniasis (CL) is unknown. Immunological evidence of exposure to Leishmania in residents of endemic areas has been the basis for defining the human population with asymptomatic infection. However, parasitological confirmation of subclinical infection is lacking. METHODS:We investigated the presence and viability of Leishmania in blood and non-invasive mucosal tissue samples from individuals with immunological evidence of subclinical infection in endemic areas for CL caused by Leishmania (Viannia) in Colombia. Detection of Leishmania kDNA was conducted by PCR-Southern Blot, and parasite viability was confirmed by amplification of parasite 7SLRNA gene transcripts. A molecular tool for genetic diversity analysis of parasite populations causing persistent subclinical infection based on PCR amplification and sequence analysis of an 82bp region between kDNA conserved blocks 1 and 2 was developed. PRINCIPAL FINDINGS:Persistent Leishmania infection was demonstrated in 40% (46 of 114) of leishmanin skin test (LST) positive individuals without active disease; parasite viability was established in 59% of these (27 of 46; 24% of total). Parasite burden quantified from circulating blood monocytes, nasal, conjunctival or tonsil mucosal swab samples was comparable, and ranged between 0.2 to 22 parasites per reaction. kDNA sequences were obtained from samples from 2 individuals with asymptomatic infection and from 26 with history of CL, allowing genetic distance analysis that revealed diversity among sequences and clustering within the L. (Viannia) subgenus. CONCLUSIONS:Our results provide parasitological confirmation of persistent infection among residents of endemic areas of L. (Viannia) transmission who have experienced asymptomatic infection or recovered from CL, revealing a reservoir of infection that potentially contributes to the endemicity and transmission of disease. kDNA genotyping establishes proof-of-principle of the feasibility of genetic diversity analysis in previously inaccessible and unexplored parasite populations in subclinically infected individuals.